Endothelial Ephrin‐B2 is Essential for Arterial Vasodilation in Mice. (October 2014) - Lin, Yuankai; Jiang, Weiya; Ng, Jennifer; Jina, Asmita; Wang, Rong A.
Abstract Objective The cell surface protein ephrin‐B2 is expressed in arterial and not venous ECs throughout development and adulthood. Endothelial ephrin‐B2 is required for vascular development and angiogenesis, but its role in established arteries is currently unknown. We investigated the physiological role of ephrin‐B2 signaling in adult endothelium. Methods We generated adult conditional knockout mice lacking the Efnb2 gene specifically in ECs and evaluated the vasodilation responses to blood flow increase and ACh in the cremaster muscle preparation by intravital microscope and in carotid artery by in vivo ultrasound. Results We found that the Efnb2 conditional knockout mice were defective in acute arterial dilation. Vasodilation was impaired in cremaster arterioles in response to either increased flow or ACh, and in the carotid arteries in response to increased flow. Levels of cGMP, an effector of NO, were diminished in mutant arteries following ACh stimulation. GSNO, a donor for the vasodilator NO, alleviated the vasodilatory defects in the mutants. Immunostaining showed that a subset of ephrin‐B2 proteins colocalized with caveolin‐1, a negative regulator of eNOS. Conclusions Our data suggest that endothelial ephrin‐B2 is required for endothelial‐dependent arterial dilation and NO signaling in adult endothelium.